Uji Aktivitas Antibakteri Ekstrak Etanol Umbi Smilax Celebica Terhadap Pertumbuhan Staphylococcus Aureus ATCC 35923 Dan Shigella Flexneri ATCC 12022 - Muhamad Agil (Fak. Saintek UIN SUKA, 2011)
st,1/WS